Exploring Musical Heritage: Composition of an Original Jazz Ballad - Wattenbarger, Josiah Wade (East Carolina University, 2022)
Jazz music and its development is a significant staple in the history of American culture. Despite its decline in prevalence in modern popular culture, jazz remains an influence on music in many ways that often go unappreciated. In an effort to further explore this musical heritage through my Signature Honors Project, I composed an original jazz ballad over the course of my final two semesters at East Carolina University. The process began with building upon the foundational knowledge required to compose a jazz ballad. I entered the project with some basic music composition experience from my 10 years prior as a musician, but this was by far the largest composing endeavor I have taken up and required further expanding of my knowledge on certain concepts. In collaboration with the Jazz ensemble at ECU, my mentors guided me through reviewing music composition fundamentals, learning the processes of using the music notation software, completing practice composition exercises, and exploring the history and styles of classic Jazz ballads. With this refined knowledge at hand, I then composed a rough draft of my ballad and collaborated with several musician peers in order to find the balances of harmony and instrumentation for my final product. The final composition was produced into a recording using music production software. I aspire for this piece to be something that myself and my peers can appreciate as a tangible expression of human emotion through music as well as a preservation of jazz culture.
Keywords: Jazz; Ballad; Music Composition